As transformações estéticas da periferia nos videoclipes do rap paulistano - Santos, Leonardo Ribeiro (2017)
This term paper explores the aesthetic transformations in the representations of the dodgy area in São Paulo on music videos of RAP in the last decades. Each music video builds an imaginary world, inspired by a real world, using languages and audiovisual techniques to encode symbolically the translation of a world view. For this reason, this analysis focus on exploration of two music videos whose authors stand out in RAP scenario of São Paulo. They are: Racionais MC's and Rincon Sapiência. The theoretical-methodological framework includes concepts of Peircean semiotics and psychoanalysis. The research sought to understand how those music videos express and translate the representations of the dodgy areas of São Paulo, considering its aesthetic, imaginary and symbolic views. The main authors who contributed to this study were Santaella, Nöth, Machado, Soares, Teperman, Bauman and Cesarotto. The first Chapter presents a historical overview of RAP and music video, to contextualize their beginning, connections and expansions. At first, we introduced the RAP history, after that, we presented the music video history, highlighting authors and the main concepts for analyzing their music videos. In chapter 2, we performed the semiotic analysis of music videos "Vida Loka Part II", by Racionais MC's, and "A coisa tá Preta" by Rincon Sapiência. We explored aspects related to the three peircean categories (firstness, secondness and thirdness) in each music video. Finally, we compare the differences and similarities between both, in order to show that aesthetic transformations occurred with them and how imaginary and symbolic aspects are associated with the respective world views that could be translated by each production. Then, we conclude the term paper presenting the final considerations